The effect of palm oil clinker and oil palm shell on the compressive strength of concrete - Alaa A., Shakir; Wan Ibrahim, M. H; Shahidan, S (Springer Nature, 2018)
This article reviews the physical, chemical and microstructural properties of palm oil clinker (POC) and oil palm shell (OPS) by-products of palm oil. They are considerably used as lightweight aggregate to produce lightweight concrete so as to conserve the virgin resources and to reduce environmental contamination, whereby sustainability will be achieved. This paper is devoted to explaining the compressive strength behavior of concrete incorporating POC and OPS as lightweight aggregate. It is demonstrated that POC of size below 4.75 mm can be used as a partial fine aggregate replacement. Coarse POC sized 9–4.75 mm can be used as coarse aggregate substitution. POC powder (POCP) showed an improvement in compressive strength of concrete when used as filler. POCP treated at 850 C showed a distinct increase in compressive strength when added as 30% by weight of cement. Previous studies have investigated the possibility of using OPS as the coarse aggregate replacement in concrete after following certain treatments. However, they have also documented a significant drop in compressive strength of concrete due to the smooth texture surface of the convex and concave of shells, hence weakening the bond between aggregate and mortar. Consequently, the compressive strength of concrete is reduced. On the contrary, coarse POC showed a compressive strength development when used as OPS substitution. Future studies should focus on OPS treatments to remove purities and develop bond strength in concrete. Future investigations should consider a broader usage of POC and OPS as lightweight aggregate in other applications like mortar, tiles, bricks and blocks. All in all, the usage of oil palm by-products as lightweight aggregate has recorded an accepted compressive strength for lightweight concrete.